Analisis Akuntansi Pencatatan dan Penilaian Persediaan Barang Berdasarkan PSAK 14 pada Toko Buku Toha Putra Medan - Lubis*, Rizkia Rahmadani; Nasution, Minasari (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Toha Putra Medan Bookstore is a company whose activities are engaged in wholesale and distribution of Islamic books, Al-Qur'an and translations, English-Indonesian dictionaries. The purpose of this research is to determine the suitability of the application of the method of recording and evaluating merchandise at the Toha Putra Medan Bookstore with PSAK No. 14 About supplies. The data collection methods used were documentation, literature study, observation techniques and interviews. The data analysis technique uses a combination of qualitative and quantitative analysis with recording used using the perpetual method, while inventory valuation uses the FIFO (First in First Out) method or first in, first out. The research results showed that the recording and assessment of inventory at the Toha Putra Medan Bookstore was in accordance with PSAK No. 14 regarding supplies. It is hoped that the Toha Putra Medan Bookstore will maintain the method used because it is in accordance with PSAK No.14.